Bioherder Generated by Rhodococcus erythropolis as a Marine Oil Spill Treating Agent - Yu, Miao; Zhu, Zhiwen; Chen, Bing; Cao, Yiqi; Zhang, Baiyu (Frontiers in Microbiology, 2022)
There is an urgent call for contingency planning with effective and eco-friendly oil spill cleanup responses. In-situ burning, if properly applied, could greatly mitigate oils at waters and minimize the adverse environmental impacts of spilled oils. Chemical herders have been commonly used along with in-situ burning to increase the thickness of spilled oil at sea and facilitate combustion. These chemical surfactant-based agents can be applied at the edges of the oil slick and increase the slick thickness by reducing the water-oil interface tension. Biosurfactants have been recently developed as the next generation of herds with less environmental footprint. In this study, a biosurfactant produced by Rhodococcus erythropolis M25 was evaluated and demonstrated as an effective herding agent. The impact of environmental and operational factors (e.g., temperature, herder dose, spilled oil amount, water salinity, and operation location) on its performance were investigated. A five-factor fractional design was applied to examine the importance of these factors and their impact on herding effectiveness and efficiency. The results of this study showed that a higher temperature and a higher dose of herder could result in an increased oil slick thickness changing rate. Different water salinity under the same temperature led to the same trend; that is, the herding effectively goes up with the increase of herder-oil ratio. Large-scale testing needs to be further conducted for evaluating the applicability of the developed bioherder in the field.